Is there an “intergenerational gap” in transport usage? Comparing transport preferences of seniors and students - Kos-Łabędowicz, Joanna (Czy występuje zjawisko przepaści międzypokoleniowej w preferencjach transportowych? Porównanie preferencji transportowych seniorów i studentów, 2019)
The purpose of this paper is to examine the transport preferences of seniors and to identify potential differences in their use of transport compared to those of a younger generation, utilising literature analysis and subsequent descriptive and statistical analyses of data. The article outlines the problem of an ageing society and indicates factors important for the elderly when using the transport system. The results of direct research concerning the declared preferences of seniors and students in the choice of means of transport depending on the destination are presented. Seniors indicated public transport most often, but most people who could use a car preferred that choice for at least one of their destinations. For students, both car and public transport were also the two most frequently chosen means of transport. Despite the limited comparability of both groups, two issues are noteworthy – the similar proportions of preference for individual travel destinations, and the means of transport with definitely different levels of possibility of using a car. This suggests that in the case of seniors we are dealing with behaviour resulting from reasons other than transport preferences
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 58-70
Keywords: transport preferences; transport behaviours; seniors; ageing society; preferencje transportowe; zachowania transportowe; seniorzy; starzejące się społeczeństwo; studenci; students